2014
DOI: 10.1021/jp501472s
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Diffusion Studies of Water Self-Diffusion in Supercooled Aqueous Sodium Chloride Solutions

Abstract: The physical properties of aqueous sodium chloride solutions have been studied theoretically, but so far no experimental diffusion data have been obtained under supercooled conditions. Here the results of (1)H NMR translational diffusion measurements of water in sodium chloride solutions in the temperature range 230 to 300 K and sodium chloride concentrations up to 4.2 mol/kg are presented. It was found that the diffusion data were well-described by the Vogel-Tamman-Fulcher relationship with concentration-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…First, we obtained a diffusion coefficient of H 2 O at 298.15 K, D = 2.058 × 10 −9 m 2 ·s −1 , which was almost identical to another Pulsed Gradient Spin-Echo (PGSE) NMR result (2.11 ± 0.20 × 10 −9 m 2 ·s −1 ) acquired under the same condition [ 26 ]. However, the diffusion coefficient of D 2 O (1.762 × 10 −9 m 2 ·s −1 ) obtained here was much smaller than that of H 2 O.…”
Section: Resultssupporting
confidence: 68%
“…First, we obtained a diffusion coefficient of H 2 O at 298.15 K, D = 2.058 × 10 −9 m 2 ·s −1 , which was almost identical to another Pulsed Gradient Spin-Echo (PGSE) NMR result (2.11 ± 0.20 × 10 −9 m 2 ·s −1 ) acquired under the same condition [ 26 ]. However, the diffusion coefficient of D 2 O (1.762 × 10 −9 m 2 ·s −1 ) obtained here was much smaller than that of H 2 O.…”
Section: Resultssupporting
confidence: 68%
“…The 1 H NMR study of water diffusion in sodium chloride solutions have shown that the activation energy can increase up to 40 kJ/mol or even higher, depending on temperature and concentration. 43 The higher activation energy in PMETAC can be understood accepting the vehicle mechanism, i.e., the main proton carriers are H 3 O + ions that move via the heterogeneous medium that consists of the organic framework and ionic N + and Cl – substructure ( Figure 8 ). Moreover, the presence of relatively narrow (∼180 Hz) peak in the 1 H MAS NMR spectrum at 4.5 ppm confirms a high mobility of water and other −OH containing species in wet PMETAC (Supporting Information, Figure S1 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…To do so, we had to develop a parameterization of water diffusivity based on the data published by Garbacz and Price. 58 To reduce the level of uncertainty associated with this parameterization, we constrained the parametrization by requiring it to follow the self-diffusivity of pure water recently made available for temperature range down to 220 K. 60 Nevertheless, the extrapolation of this parameterization beyond available experimental data should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%